2016
DOI: 10.1111/jfpp.12779
|View full text |Cite
|
Sign up to set email alerts
|

Roasting, Grinding, and Storage Impact on Thermodynamic Properties and Adsorption Isotherms of Arabica Coffee

Abstract: This work aimed to evaluate alterations on the water sorption of coffee due to roast, grind, and storage. Crude grain coffee (Coffea arabica) was roasted at two levels: medium light and moderately dark. Grain was grinded in fine (0.59 mm), medium (0.84 mm), and coarse (1.19 mm) particle sizes, besides the whole coffee lot. Samples were then stored at polypropylene bags and kept at biochemical oxygen demand type chambers in two storage temperatures (10 and 30C). These were analyzed at 0, 30, 60, 120, and 180 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
(43 reference statements)
3
18
0
Order By: Relevance
“…[30] ΔG increases with the equilibrium moisture content and temperature for dried cocoa beans in all moisture content ranges, and for roasted cocoa beans, at equilibrium moisture contents up to 0.028 kg·kg −1 d.b., indicating that the lower the temperature, the more spontaneous the adsorption process of dried and roasted cocoa beans (Figure 3c,d). [6] Similar results corresponded with the studies in ground-roasted coffee by Oliveira et al [9] , microencapsulated extra virgin olive oil by Bastioğlu et al [6] , and whole black peppercorns by Yogendrarajah et al [13] However, the crossing trend of Gibbs free energy with temperature ( Figure 3d) at equilibrium moisture contents higher than 0.029 kg kg −1 d.b., corresponding to a w > 0.8, can be explained by the change in sorption properties at high water activities due to the dissolution of sugars in water (endothermic process), which was according to the behavior observed in (Figure 1b).…”
Section: Mathematical Expressionsupporting
confidence: 88%
See 1 more Smart Citation
“…[30] ΔG increases with the equilibrium moisture content and temperature for dried cocoa beans in all moisture content ranges, and for roasted cocoa beans, at equilibrium moisture contents up to 0.028 kg·kg −1 d.b., indicating that the lower the temperature, the more spontaneous the adsorption process of dried and roasted cocoa beans (Figure 3c,d). [6] Similar results corresponded with the studies in ground-roasted coffee by Oliveira et al [9] , microencapsulated extra virgin olive oil by Bastioğlu et al [6] , and whole black peppercorns by Yogendrarajah et al [13] However, the crossing trend of Gibbs free energy with temperature ( Figure 3d) at equilibrium moisture contents higher than 0.029 kg kg −1 d.b., corresponding to a w > 0.8, can be explained by the change in sorption properties at high water activities due to the dissolution of sugars in water (endothermic process), which was according to the behavior observed in (Figure 1b).…”
Section: Mathematical Expressionsupporting
confidence: 88%
“…Similar isotherm forms and equilibrium moisture content values were reported in dried cocoa beans by Herman et al [19] and in cocoa coatings by Meza et al [20] ; moreover, the authors attributed the trend as representative of most food products rich in soluble components, such as sugars. Other agricultural products with sigmoid-shaped forms include roasted coffee, reported by Baptestini et al [21] ; Oliveira et al [9] , microencapsulated extra virgin olive oil, reported by Bastioğlu et al [6] , spray-dried fat-filled pea protein-based powders, reported by Domian et al [10] , and whole black peppercorns, reported by Yogendrarajah et al [13] It is widely accepted that at constant water activity, an increase in temperature causes a decrease in the amount of sorbed water [10] because the temperature affects the mobility of water molecules and the dynamic equilibrium between the vapor and adsorbed phases. [13] (Figure 1a) shows the effect of temperature on the adsorption isotherms of dried cocoa beans; an increase in temperature causes a decrease in the equilibrium moisture content at constant water activity, and there were statistically significant differences (95%) from water adsorption isotherms at 25, 30 and 40°C in all ranges of a w , as confirmed by analysis of variance.…”
Section: Mathematical Expressionmentioning
confidence: 99%
“…This same response was observed by Oliveira, Corrêa, Oliveira, Baptestini, and Vargas-Elías (2016). The author explained that water adsorption occurred in vapor form, since the energy released by the process did not reach the value of the latent heat of condensation.…”
Section: Acta Scientiarum Agronomysupporting
confidence: 60%
“…The legal moisture limit for storing and conserving the quality of whole and ground coffee beans is 5% to 5.26% (dry basis) (Brasil, ). The moisture level of roasted whole or ground coffee also depends upon the roast level and particle size of ground coffee (Melo, ; Oliveira, Correa, Oliveira, Baptestini, & Vargas‐elias, ; Schmidt et al., 2008). Similarly, storage period, along with the variables of roasting and particle size, significantly influences the moisture content of all coffee types at both low and high storage temperatures.…”
Section: Storagementioning
confidence: 99%